Rethinking fiscal policy:lessons from the European Monetary Union (EMU) - Saraceno, Francesco (Geneva, 2017)
"This paper gives an assessment of the current state of the debate on fiscal policy effectiveness. I begin with an account of the theory of fiscal policy, and how it has evolved from the pre-Keynesians to the emergence of a “New Consensus” that dominated theory (and policy-making) until the crisis of 2008. Fiscal policy, a critical underpinning behind the full employment policies of the Post-WWII period, was removed from the policy-makers’ toolbox by the New Consensus, and preference given to rules over discretion in government interventions. The paper then highlights how the Economic and Monetary Union of the European Union (EMU) is an incarnation of the New Consensus, and argues that this had a rather negative impact on the growth performance of the Eurozone. The Stability and Growth Pact, the EMU fiscal rule, is then dissected to conclude that it is far from optimal even if it was never really applied. The paper then shows how the crisis has shaken the Consensus, and is leading to a reassessment of the utility of fiscal policy."